Syndecans and Enzymes Involved in Heparan Sulfate Biosynthesis and Degradation Are Differentially Expressed During Human Odontogenesis - Kero, Darko; Bilandzija, Tanja Simic; Arapovic, Lidija Lasic; Vukojevic, Katarina; Saraga-Babic, Mirna (Frontiers in Physiology, 2018)
Syndecans belong to a four-member family of cell surface heparan sulfate proteoglycans (HSPGs) abundantly present in various tissues. They are primarily recognized as extracellular matrix (ECM) receptors able to bind various ECM components and form gradients of morphogens and growth factors. Syndecans are composed of core protein with distinctive cytoplasmic, transmembrane, and extracellular domains to which several HS glycosaminoglycan (GAG) chains are covalently attached. In development of composite organs, such as teeth, expression patterns of syndecans display temporo-spatial shifts between epithelial and mesenchymal tissue compartments. Along with diverse functional properties of syndecans and generally large number of their interactors due to HS GAG chain content, this suggests possible involvement of syndecans in modulation of epithelial-to-mesenchymal crosstalk. Functional versatility of syndecans greatly depends upon the biochemical properties of attached HS GAG chains. These are specifically determined during the HS biosynthesis by the combinatorial action of glycosyl-transferases (Exts/EXTs) and bi-functional sulfotransferases (Ndsts/NDSTs), as well as by post-biosynthetic enzymatic cleavage of HS by the only active endoglucuronidase in mammals, heparanase 1 (Hpse1/HPSE1). Matching the essential requirement for HS during organogenesis, null-mutant animals for genes encoding these enzymes display severe developmental anomalies of mineralized tissues (including teeth) with embryonic or perinatal lethality. In this study, we analyzed expression of syndecan HSPGs (syndecans 1, 2, and 4), enzymes involved in HS biosynthesis (EXT1, NDST1, NDST2) and HS cleavage (HPSE1) in human tooth germs during the early stages of odontogenesis. All of the investigated factors displayed temporo-spatial differences in expression patterns, and some of them showed distinctive asymmetries of expression domains. Our findings suggest that these factors might be differentially involved in cellular processes which take place during the early odontogenic sequence in humans.